A brief introduction to the philosophy of meta-reality (Polifonia, 2016)
Bhaskar’s Philosophy of meta-Reality (PMR) referred to as his spiritual turn, first began with his book From East to West: Odyssey of a Soul (2015b the second edition), and continued within the three main books of meta-Reality. This paper attempts to place PMR within the stream of Critical Realism (CR) and introduce to the reader two of the most importance elements of PMR, nonduality and the theory of transcendence. PMR further suggests that the serious of our philosophy in theory and practice comes from the account that it can make for its power of emancipation.Keywords: Spirituality, meta-Reality, Bhaskar